Implementation of Technology-Based Integrated Learning (ICT) in Primary Schools - Andriyani, Fitri; Harahap, Nurmaini (International Journal of Students Education, 2023)
The thematic learning model began to be discussed by education experts in 1999. Thematic learning which refers to KBK and KTSP has been implemented since 2005. According to Fogarty, there are 10 types of thematic models, but only 3 have been studied by Indonesian education experts, namely the spider web type thematic learning model, the integrated type thematic learning model and the connectedness model thematic learning model. Thematic learning is a teaching and learning approach that involves several subjects in one theme to provide meaningful experiences for students. Meaningful experience means that children understand the concepts they have learned through direct experience and connect them with other concepts they already understand. To implement thematic learning in elementary schools, there are several components that need to be discussed first, such as methods, assessment, media, learning steps and the role of the teacher. After that, we will discuss the steps for preparing thematic learning as well as examples of the thematic matrix, syllabus and lesson plans.